Євангельські християни святі сіоністи: особливості життя й побуту - Скакун, Р. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
У статті Р. Скакуна розглянуто, особливості життя, побуту й релігійного культу євангельських християн святих сіоністів („мурашковців”), громада яких існує в смт. КомінтернівськеОдеської області. Ключові слова: євангельські християни святі сіоністи, мурашковці, юдаїстичний культ, субота, заповіді, релігійна громада. The article discusses a sectarian group of the Evangelical Christians Saint Zionists, also known as Murashkovtsi, which presently exists as a community of 435 people in the town of Kominternivske, Odessa region. The peculiar features of the group, which emerged in early 1930’s from the popular Pentecostalism, include its mystical and ecstatic cult, which gradually declines, and its judaistic system of practical ritualistic prescriptions. The group is also characterized by endogamy, strong solidarity and the persisting model of traditional extended family. Keywords: Evangelical Christians Saint Zionists, Murashkovtsi, judaistic cult, Sabbath, ritualistic prescriptions, religious community.